Computer-assisted navigation for intramedullary nailing of intertrochanteric femur fractures: a preliminary result - Michele Coviello; Francesco Ippolito; Antonella Abate; Giacomo Zavattini; Domenico Zaccari; Andrea Leone; Giovanni Noia; Vincenzo Caiaffa; Giuseppe Maccagnano (Medicinski glasnik, 2022)
Aim: To demonstrate a reduction of risk factors ray-depending in proximal femur nailing of intertrochanteric femur fractures, comparing standard technique with computer-assisted navigation system. Methods: One hundred patients hospitalised between October 2021 and June 2022 with intertrochanteric femur fractures type 31-A1 and 31-A2 were prospectively enrolled and divided randomly into two groups. A study group was treated with computer-assisted navigation system ATLAS (Masmec Biomed, Modugno, Bari, Italy) (20 patients), while a control group received the standard nailing technique. The same intertrochanteric nail was implanted by a single senior surgeon, Endovis BA 2 (EBA2, Citieffe, Calderara di Reno, Bologna, Italy). The following data were recorded: the setup time of operating room (STOR; minutes); surgical time (ST; minutes); radiation exposure time (ETIR; seconds) and dose area product (DAP; cGy·cm2). Results: Patients underwent femur nailing with computer-assisted navigation system reported more set-up time of operating room (24.87±4.58; p<0.01), less surgical time (26.15±5.80; p<0.01), less time of radiant exposure (4.84±2.07; p<0.01) and lower dose area product (16.26±2.91; p<0.01). Conclusion: The preliminary study demonstrated that computerassisted navigation allowed a better surgical technique standardization, significantly reduced exposure to ionizing radiation, including a reduction in surgical time. The ATLAS system could also play a key role in residents improving learning curve.
Keywords: computer-assisted surgery; fluoroscopy; internal fixation; intertrochanteric fracture; nailing